(untitled) (Al-Mansour Journal, 2025)
The study aims to present the most significant threats facing the Iraqi hotel sector in order to achieve cybersecurity, which plays a pivotal role in addressing future challenges, given its use as a technology for managing hotel organizations’ networks. The objective is to develop mechanisms to mitigate these threats and take all necessary precautionary measures to prevent any potential destabilization of hotel organizations. While technology has contributed significantly to the development of the hotel sector and facilitated access to and utilization of its services, it has also had negative consequences — namely, the threat of cyberattacks, data breaches, and unauthorized access to the organizations’ information systems. This poses a serious risk not only to hotel organizations themselves but also to the privacy and safety of their customers’ information. Therefore, this study seeks to explore the concept of cybersecurity and identify the main threats that may face the Iraqi hotel sector. The study concludes that there is a negative impact on hotel performance and reputation: any breach, data leak, or cyberattack can result in financial losses, loss of customer trust, and legal consequences — all of which weaken competitiveness and harm business operations, especially in a sector that relies heavily on customer service and trust. The study recommends the establishment of clear and consistent security policies: adopting an information security policy that ensures data confidentiality, customer privacy, security updates, and controlled user access.